Arterioureteral fistula: overview of clinical characteristics, endovascular management, and outcomes. Issue 2 (1st February 2022) - Noh, Seung Yeon; Shin, Ji Hoon; Yang, Woo Jin; Chu, Hee Ho; Park, Suyoung; Chen, Chengshi; Lee, Woong Hee
Abstract: Background: Arterioureteral fistula (AUF) is a condition resulting from the pathologic connection between the ureter and the artery. Despite the low incidence, it can lead to devastating clinical consequences due to massive hematuria with a considerable mortality rate. Material and methods: From January 2009 to December 2018, eight patients with AUF from two tertiary referral centers were included. Clinical data including presenting symptoms, previous pelvic surgery or radiotherapy, indwelling ureteral stents, primary vascular pathology, angiographic findings, type of treatment, survival, and recurrence were analyzed. Results: All eight patients (six women, mean age 62.4 ± 14.5 years) presented with macroscopic hematuria and were successfully treated by endovascular management. One patient developed AUF due to an underlying iliac artery aneurysm, and the rest were due to secondary causes. Six patients had a history of an indwelling ureteral stent for a median of 5.5 months (1–84 months). All of the patients were successfully treated by endovascular management. For the median follow up of 987 days, three patients had recurrence of hematuria in a mean of 6.3 months, two patients were treated by surgery, while one was treated by endovascular treatment. Conclusion: AUF should be confirmed through a purposeful iliac angiogram or ureterography when suspected based on a relevant history or CT findings. AUF can be successfully treated by endovascular management. The surgical option should be considered in cases of recurrence. Abbreviations: AUF: arterioureteral fistula; CIA: common iliac artery; DJ: double J; EIA: external iliac artery; IIA: internal iliac artery; NBCA: N-butyl cyanoacrylate; PCN: percutaneous nephrostomy